The Effect of Oral Immunomodulatory Therapy on Treatment Uptake and Persistence in Multiple Sclerosis - Warrender-Sparkes, M.; Spelman, T.; Izquierdo, G.; Trojano, M.; Lugaresi, A.; Grand'Maison, F.; Kubala Havrdová, E. (SAGE Publications Ltd info@sagepub.co.uk, 2016)
Objective: We aimed to analyse the effect of the introduction of fingolimod, the first oral disease-modifying therapy, on treatment utilisation and persistence in an international cohort of patients with multiple sclerosis (MS). Methods: MSBASIS, a prospective, observational sub-study of the MSBase registry, collects demographic, clinical and paraclinical data on patients followed from MS onset (n=4718). We conducted a multivariable conditional risk set survival analysis to identify predictors of treatment discontinuation, and to assess if the introduction of fingolimod has altered treatment persistence. Results: A total of 2640 patients commenced immunomodulatory therapy. Following the introduction of fingolimod, patients were more likely to discontinue all other treatments (hazard ratio 1.64, p<0.001) while more patients switched to fingolimod than any other therapy (42.3% of switches). Patients switched to fingolimod due to convenience. Patients treated with fingolimod were less likely to discontinue treatment compared with other therapies (p<0.001). Female sex, country of residence, younger age, a high Expanded Disability Status Scale score and relapse activity were all independently associated with higher rates of treatment discontinuation. Conclusion: Following the availability of fingolimod, patients were more likely to discontinue injectable treatments. Those who switched to fingolimod were more likely to do so for convenience. Persistence was improved on fingolimod compared to other medications. © SAGE Publications.
Keywords: Disease-Modifying Therapy; Fingolimod; Medication Persistence; MSBase; Multiple Sclerosis